2017
DOI: 10.1371/journal.pone.0174247
|View full text |Cite
|
Sign up to set email alerts
|

Linking phenological events in migratory passerines with a changing climate: 50 years in the Laurel Highlands of Pennsylvania

Abstract: Advanced timing of both seasonal migration and reproduction in birds has been strongly associated with a warming climate for many bird species. Phenological responses to climate linking these stages may ultimately impact fitness. We analyzed five decades of banding data from 17 migratory bird species to investigate 1) how spring arrival related to timing of breeding, 2) if the interval between arrival and breeding has changed with increasing spring temperatures, and 3) whether arrival timing or breeding timing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Within the same species, flexible adjustment to earlier springs seemed to be realised by shortening the arrival-breeding interval (Nicolau et al, 2021). McDermott and DeGroote (2017) analysed data on 17 migratory species, and found a positive relationship between earlier arrival at the breeding grounds and earlier breeding in four species, whereas in six species, the arrival-breeding interval shortened in warmer springs, as occurred in our Alpine wheatear population in 2020 (Figure 2B).…”
Section: Discussionmentioning
confidence: 57%
“…Within the same species, flexible adjustment to earlier springs seemed to be realised by shortening the arrival-breeding interval (Nicolau et al, 2021). McDermott and DeGroote (2017) analysed data on 17 migratory species, and found a positive relationship between earlier arrival at the breeding grounds and earlier breeding in four species, whereas in six species, the arrival-breeding interval shortened in warmer springs, as occurred in our Alpine wheatear population in 2020 (Figure 2B).…”
Section: Discussionmentioning
confidence: 57%
“…As long-term changes in laying dates are related to body size [38], we also predict that small-bodied species will change the duration of their seasons more significantly in comparison with larger species [38,39]. Finally, previous studies suggested that long-distance migrants may be constrained in their phenological response to climate change [40][41][42][43], thus we may expect that the duration of their breeding season will change less across time, in comparison with short-distance migrants or sedentary species.…”
Section: Introductionmentioning
confidence: 64%
“…Therefore, our study may provide a new argument in support of the phenologymismatch hypothesis [71], which assumes that the rate of warming in the breeding and wintering areas need not to be correlated, causing a delayed departure from wintering sites and ecological mismatch at the breeding sites. Several other studies have also shown that although long-distance migrants have been arriving progressively earlier in response to climate warming [41,42] and the interval between arrival and breeding has shortened [40,43], their breeding phenology has been actually delayed in relation to plant or insect phenology [35,40,41].…”
Section: Discussionmentioning
confidence: 98%
“…This result suggests that air temperature was the main factor activating the endocrine control of spring migration in wintering whooper swans. Numerous studies have reported on the effects of photo period 5 , 11 – 14 or ambient temperature 42 47 on the spring migration of palae-arctic migrants. Since both parameters are inevitably linked—even in our study we found a strong correlation of both factors—it was proposed that both environmental factors influence the departure from wintering areas by influencing the endocrine control mechanisms 48 , 49 .…”
Section: Discussionmentioning
confidence: 99%